Thiotepa-busulfan-fludarabine as a conditioning regimen for patients with myelofibrosis undergoing allogeneic hematopoietic transplantation: a single center experience. Issue 2 (28th January 2021) - Memoli, Mara; Paviglianiti, Annalisa; Malard, Florent; Battipaglia, Giorgia; Brissot, Eolia; Médiavilla, Clémence; Bianchessi, Antonio; Banet, Anne; Van de Wyngaert, Zoé; Ledraa, Tounes; Belhocine, Ramdane; Sestili, Simona; et al.
Abstract: We assessed the outcomes associated with thiotepa, busulfan and fludarabine (TBF) conditioning regimen in a cohort of 29 consecutive patients allografted for myelofibrosis (MF). The median age was 56 (range 42–70) years. According to the refined Dynamic International Prognostic Scoring System (DIPSS-plus), 15 (52%) patients were classified as high risk. Graft source was peripheral blood stem cells in 27 patients. Donor type was HLA-matched related ( n  = 5), matched unrelated ( n  = 16), mismatched unrelated ( n  = 1), and haploidentical ( n  = 7). All but 2 patients engrafted. The cumulative incidence (CI) of grade II–IV acute graft-versus-host disease (GVHD) was 21% (95% CI, 10–42) at day 100. The CI of chronic GVHD was 39% (95% CI, 23–65) at 3 years. The median follow-up period was 39 (range 14–60) months. Overall survival was 69% (95% CI, 50–83) at 3 years. No relapse was observed. TBF is a valid conditioning strategy in patients with MF.